Dystrobrevin alpha gene is a direct target of the vitamin D receptor in muscle. (April 2020) - Tsoumpra, Maria K; Sawatsubashi, Shun; Imamura, Michihiro; Fukumoto, Seiji; Takeda, Shin'ichi; Matsumoto, Toshio; Aoki, Yoshitsugu
Abstract : The biologically active metabolite of vitamin D, 1, 25-dihydroxyvitamin D3 (VD3), exerts its tissue-specific actions through binding to its intracellular vitamin D receptor (VDR) which functions as a heterodimer with retinoid X receptor (RXR) to recognize vitamin D response elements (VDRE) and activate target genes. Upregulation of VDR in murine skeletal muscle cells occurs concomitantly with transcriptional regulation of key myogenic factors upon VD3 administration, reinforcing the notion that VD3 exerts beneficial effects on muscle. Herein we elucidated the regulatory role of VD3/VDR axis on the expression of dystrobrevin alpha (DTNA), a member of dystrophin-associated protein complex (DAPC). In C2C12 cells, Dtna and VDR gene and protein expression were upregulated by 1–50 nM of VD3 during all stages of myogenic differentiation. In the dystrophic-derived H2K-mdx52 cells, upregulation of DTNA by VD3 occurred upon co-transfection of VDR and RXR expression vectors. Silencing of MyoD1, an E-box binding myogenic transcription factor, did not alter the VD3-mediated Dtna induction, but Vdr silencing abolished this effect. We also demonstrated that VD3 administration enhanced the muscle-specific Dtna promoter activity in presence of VDR/RXR only. Through site-directed mutagenesis and chromatin immunoprecipitation assays, we have validated a VDRE site in Dtna promoter in myogenic cells. We have thus proved that the positive regulation of Dtna by VD3 observed during in vitro murine myogenic differentiation is VDR mediated and specific. The current study reveals a novel mechanism of VDR-mediated regulation for Dtna, which may be positively explored in treatments aiming to stabilize the DAPC in musculoskeletal diseases.